On proper accretive extensions of positive linear relations - Arlinskii, Yu.M. (Український математичний журнал, 1995)
A linear relation Ŝ is called a proper extension of a symmetric linear relation S if S ⊂ Ŝ ⊂ S*. As is well known, an arbitrary dissipative extension of a symmetric linear relation is proper. In the present paper, we establish criteria for an accretive extension of a given positive symmetric linear relation to be proper.